FACTORS THAT INFLUENCE CUSTOMER BUYING INTEREST: CASE STUDY OF SHOPEE AND TIKTOK SHOP MARKETPLACE - Hanafiah, Hafidz; Susanto, Budi; Alamsyah, Alamsyah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The increasing use of internet technology along with the development of the era has become a lifestyle for some people in Indonesia. So that it encourages marketers to create the right marketing strategy for the company. The purpose of this study is to determine the effect of live sales streamings, product reviews, and discounts on buying interest in the Shopee marketplace. And to determine the effect of influencer marketing, product quality, and product diversity on buying interest in online shopping at TikTok Shop. This study uses a quantitative research approach, which is a scientific method because it has met scientific principles in a concrete or empirical, objective, measurable, rational, and systematic manner. The data used are primary and secondary data which are then processed using SPSS 26. The population of this study was 50 people who were then used as samples with a saturated sampling technique. This study uses a quantitative research approach, which is a scientific method because it has met scientific principles in a concrete or empirical, objective, measurable, rational, and systematic manner. The data used are primary and secondary data which are then processed using SPSS 26. The population of this study was 50 people who were then used as samples with a saturated sampling technique. The results of the study show that the Shopee marketplace is a live sales streaming that influences purchase interest with a t-count value of 7.466> t table. Product reviews influence purchase interest with a t-count value of 11.466> t table. Discounts influence purchase interest with a t-count value of 7.077 t table. Meanwhile, the results of the study on TikTok Shop showed that based on the results of the t-test, there was an influence of influencer marketing on purchase interest with a t-count result of 4.415> t table. Product quality on purchase interest with a t-count result of 5.453> t table. Product diversity with a t-count result of 0.274 <t table had no effect on purchase interest. So it can be concluded that live sales streamings, product reviews, and discounts each have an effect on buying interest in the Shopee marketplace. As well as influencer marketing, product quality, and product diversity each have an effect on buying interest in Tiktok Shop